Selection Criteria of Hospital Volunteers for the Provision of Health Services in Disasters - Forouzandeh Jannat; Ali Ardalan; Mokhtar Malekpour; Gholamreza Masoumi; Marzieh Vahid-Dastjerdi (Health in Emergencies & Disasters Quarterly, 2017)
Background: Hospitals need volunteers to help the injured people during disasters. Thus, it is necessary to prepare some criteria for selecting volunteers. The purpose of this study was to determine and prioritize individual and social criteria for selection of local volunteers in hospitals before disasters, the volunteers who provide health services for victims in disasters. Materials and Methods: This was an analytical descriptive study in which a researcher-made questionnaire was used to collect the data in 2015. The statistical population consisted of emergency and health managers and experts in hospitals affiliated to Tehran University of Medical Sciences. The sample were selected using Cochrane methodology and calculated as 180 subjects. The data were analyzed through calculating mean, standard deviation, 1-sample t-test, and Friedman test using SPSS. Results: Based on the results, most personal and social criteria were significant (P≤0.05) and important in volunteers’ selection. The results showed that the most important personal criteria were physical ability and fitness, practical expertise, and voluntary attendance experience with the mean ranks of 4.03, 3.94, and 3.77, respectively. Also among social criteria, prompt response with the mean rank of 7.26, responsibility with 6.25, and conscience with 6.06 have been determined as important factors in the selection of volunteers for health services of hospitals in disasters. Conclusion: Hospitals could select volunteers based on the determined criteria. Personal criteria of physical fitness and practical expertise along with social criteria of prompt response and responsibility were reliable norms that based on them, the best volunteers could be chosen to perform health duties and decrease injuries in relief and health services.